Il migrante come "capro espiatorio" nei tempi odierni: il valore euristico dell'analogia - Djebbi, Sihem (Rassegna di teologia, 2025)
The analogy between the biblical figure of the scapegoat and that of the migrant in today's societies helps to better understand the mechanisms of transferring guilt and removing the scapegoat victim from society. Through the reduction of the migrant to scapegoat, the cohesion of society is safeguarded, but the ethical-philosophical foundations of our political, cultural and institutional systems are trampled underfoot.